Comparative Anesthesia Effect of Brachial Plexus Block Based on Smart Electronic Medical Ultrasound-Guided Positioning and Traditional Anatomical Positioning - Yu, Zhaoxiang (J Healthc Eng, 2021)
With the intensification of population aging, the improvement of visualization technology, and the concept of accelerated rehabilitation surgery, the anesthesia method of upper extremity surgery is gradually changing. However, these methods are often caused by anatomical variations and often have low block success rates and patient satisfaction. The neuroanatomical position should be accurately located so that the puncture needle is right next to the nerve bundle or in the nerve sheath. This is very important for implementing accurate brachial plexus anesthesia. This article uses ultrasound-guided positioning technology and traditional anatomical positioning technology for brachial plexus block treatment, aiming to explore the anesthesia effect of brachial plexus block with different techniques. This article selects 120 patients undergoing brachial plexus block surgery for forearm or hand surgery and divides these 120 patients into 6 groups with 20 people in each group. The first 3 groups were treated with brachial plexus block using ultrasound-guided positioning technology. The latter 3 groups were treated with brachial plexus block using traditional anatomical positioning technology. Experiments proved that during anesthesia, compared with the ultrasound group, the heart rate of the traditional anatomy group was significantly decreased (P < 0.05), and the average arterial pressure of the six groups of patients at each time point had no statistical difference (P > 0.05). This shows that whether it is ultrasound-guided positioning technology or traditional anatomical positioning technology, it has no effect on the average arterial pressure of the patient at each time point. In addition to intuitive and accurate viewing of needle and nerve contact, ultrasound real-time guidance allows intuitive viewing of anesthesia. This is a special advantage of nerve block under ultrasound guidance.